2016
DOI: 10.4088/jcp.15m10490
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Versus Maintaining the Dose of Olanzapine or Risperidone in Schizophrenia Patients Who Did Not Respond to a Modest Dosage

Abstract: UMIN.ac.jp/ctr/index.htm identifier: UMIN000008667.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…During pharmacotherapy for patients with schizophrenia, it is recommended that antipsychotics should be increased to an adequate dose within the tolerable range when the observed treatment response is insufficient. [1][2][3][4] However, randomized controlled trials (RCTs) and systematic reviews 5,6 have revealed conflicting reports, with little known about the optimal antipsychotic dose during the acute phase of schizophrenia. 7,8 Based on a systemic review of clinical guidelines, dosage recommendations reportedly varied based on 15 guidelines that suggest an optimal daily dose range for patients after the first psychotic episode in their acute phase 8 .…”
Section: Introductionmentioning
confidence: 99%
“…During pharmacotherapy for patients with schizophrenia, it is recommended that antipsychotics should be increased to an adequate dose within the tolerable range when the observed treatment response is insufficient. [1][2][3][4] However, randomized controlled trials (RCTs) and systematic reviews 5,6 have revealed conflicting reports, with little known about the optimal antipsychotic dose during the acute phase of schizophrenia. 7,8 Based on a systemic review of clinical guidelines, dosage recommendations reportedly varied based on 15 guidelines that suggest an optimal daily dose range for patients after the first psychotic episode in their acute phase 8 .…”
Section: Introductionmentioning
confidence: 99%
“…Once an antipsychotic is titrated to the lower end of the recommended dosing range, it becomes unclear how much additional benefit will come from increasing the dose further. In fact, a previous randomized controlled trial 16 in 2016 found that among 103 patients with schizophrenia who failed to respond to moderate doses of olanzapine or risperidone, increasing the dose further did not result in significant improvements in response rate. Additionally, the study completion rate was significantly higher in the continuation group compared to the dose increment group, demonstrating that patients who continued to have their dose increased were less likely to adhere to treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Psychopathology was assessed with the PANSS at baseline and weeks 1, 2, 4, and 6 in all studies. In this analysis, response was defined as a ≥ 25% reduction in the total PANSS score from baseline to endpoint as a 20–30% cutoff threshold has generally been employed in previous antipsychotic clinical trials .…”
Section: Methodsmentioning
confidence: 99%